Parameter optimization for photo polymerization of mask projection micro stereolithography - kamarudin, Khairu (2013)
This study presents a research on 3D part fabrication from composition of photo initiator (Phenylbis(2,4,6-trimethylbenzoyl)), photo absorber (Sudan I) and 1, 6- Hexanediol polymer effect based on curing parameters. A DLP projector was used as energy light source which initiated the photo reactive polymer at three different light source distances with three different exposed time to evaluate photoreactive polymer solidification phenomena. The experiment results obtained shows that Sudan I composition, light intensity value and exposure time of the varied photo absorber give significant effect to mechanical properties such layer thickness, dimensional accuracy, surface roughness and hardness value. These works also prove that photo absorber composition solution gave a different mechanical properties effect for 3D microstructure fabrication.